Antimicrobial and coagulating evaluation of extracts of five vegetables of ethnobotanical interest - Lopez-Villarreal, Sonia Martha; Chávez-Montes, Abelardo; Leos-Rivas, Catalina; Rodríguez-Luis, Osvelia; Castro-Ríos, Rocío; Pérez-Hernández, Raymundo (Horizonte Sanitario, 2022)
Objective: To evaluate the antimicrobial and coagulating activity from five vegetables of ethnobotanical interest extracts (Mimosa tenuiflora, Equisetum arvense, Syzygium aromaticum, Lippia graveolens and Aloe vera). Materials and methods: It was a Comparative, open, experimental, prospective and cross-sectional study through antimicrobial evaluation of the five extracts against bacterial strains of S. mutans (ATCC700611) and S. sobrinus (ATCC33478) by means of agar well technique and an evaluation of coagulating activity by measuring TP (prothrombin time) and APTT (activated partial thromboplastin time) using a coagulometer and comparing the results with those of a healthy patient. Results: It was found that the antimicrobial activity of the extracts on S. mutans at 500 and 1000ppm is statistically significant in the extracts of E. arvense and L. graveolens (p= 0.0057) and (p= 0.0000) respectively and on strains of S. sobrinus from the extracts of A. vera (p= 0.0011) and L. graveolens (p= 0.0089) in both concentrations, which show an antimicrobial effect superior to chlorhexidine. The PT patient’s (prothrombin time) value was 12.27 seconds, no statistical difference was observed with a value of (p<0.05), however, E. arvense and S. aromaticum, both at 1000ppm, presented times of 13.37 seconds and at the activated partial thromboplastin time (PTPA) the value of the patient was 32.63 seconds, highlighting M. tenuiflora at 500 ppm, which presented times of 39.17 seconds. Conclusions: The extracts described above contain chemical compounds that are valuable alternatives against microorganisms and oral treatments, and it is also very important that research suggests materials and medications that are effective in the treatment of patients and that do not represent a health risk. Keywords: Evaluation; Antimicrobial; Coagulant; Extracts